MODEL PERENCANAAN PEMBANGUNAN TERINTEGRASI ANTAR SEKTOR DI KABUPATEN GRESIK - - Sutikno; Hertoto Dwiyoso (Trunojoyo University of Madura, 2012)
The goal of this activity is to improve the quality of development planning by preparing regional development planning system (integrated regional development planning system) in Gresik. To answer these research objectives, requires a number of tools and approaches specific technical analysis, among other: (1) Location Quotient (LQ), (2) Analysis of the growth rate models (MRP), and (3) Model Input-Output (IO).The results of this study indicate: (1) economic sectors Gresik has featured as many as three sectors, namely (a) mining and quarrying; (b) processing industry; and (c) electricity, gas and water supply, (2) the sector has multiplier effect next highest are: (a) basic chemicals except fertilizers industry, (b) industry other chemical goods, and (c) basic metal industries of iron and steel, (3) the sector has the highest multiplier effect is backwards: (a) industrial goods of metal, (b) manufacture and repair ships, and (c) industrial machinery and equipment, (4) sector that has the greatest forward lingkages are: (a) basic chemicals except fertilizers industry, (b) industrial goods other chemical goods, and (c) basic metal industries of iron and steel, (5) having a backward sector lingkages most is: (a) the industrial goods of metal, (b) and ship repair industry, and (c) industrial machinery and equipment.